Software for beam diagnostics front-end systems: synchronization and implementation issues - Ludwig, M.; Chohan, V. (IEEE Conference on Real-Time Computer Applications in Nuclear Particle and Plasma Physics, 1999, 1999)
Front-end software systems used for beam diagnostics at CERN's PS accelerator complex perform control and data acquisition of local hardware components in synchronization with specific accelerator events. The principal part of the software is generally hosted in a VME crate, which drives all system components, provides interactivity with the general controls environment through networking and decouples the networking layer from the machine layer. Using three real-world examples of operational instrumentation systems, namely the beam intensity measurement between the PS-Booster and the PS, the AD Coherent Oscillations measurement and the PS Closed-Orbit Synchronization, the paper describes their synchronization to accelerator events and states. Sometimes these instrumentation systems am subject to complex real-time constraints and external conditions. The strategies to meet these requirements in the real-time software are discussed in the context of the general design and implementation in the PS control system environment.